Present Status of Shrimp Farming in Satkhira, a Southwestern District of Bangladesh (Research in Agriculture Livestock and Fisheries, 2020)
Shrimp has become one of the most important export products in recent decades due toincreasing international demand. Shrimp farming is performing significant role in thelivelihoods of rural people of southwestern part of Bangladesh which is considered thecore areas for shrimp farming. To continue the trend of exporting shrimp worldwide it isvery much needed to be familiar with the current culture practices with the precautionstaken by the shrimp farmers. A total of 30 shrimp farmers in Shyamnagarupazilla ofSatkhira district were interviewed to understand the present status of shrimp farming alongwith to identify the problems faced by the farmers, and to formulate somerecommendations for better shrimp production development. Study showed thatpolyculture was the only culture technique followed by the shrimp farmers using naturalwater sources like rain and tide. Bagda (Penaeusmondon) was the dominant culturedspecies followed by Harina (Metapenaeusmonoceros) because of their economicsignificance. Although wild post-larvae (PL) are better in quality than hatchery producedPL, farmers collected PL from both sources. Farmers usually used inorganic fertilizers likeUrea and TSP instead of organic one, but they preferred natural feeds for cost efficiencyand management purposes. The study also identified that shrimp diseases (white spot, gillrot and fin rot), lower market price, flood, high mortality and lack of scientific knowledgewere the major constraints in shrimp farming. Government, donor agencies, planners,researchers and NGOs, therefore, should come forward to assist farmers for mitigatingproblems and achieve sustainable shrimp export earnings of Bangladesh.Res. Agric., Livest. Fish.7(2): 311-320,  August 2020